A novel technique for robot assisted latissimus dorsi flap harvest. Issue 7 (July 2015) - Chung, Jae-Hyun; You, Hi-Jin; Kim, Hyon-Surk; Lee, Byung-Il; Park, Seung-Ha; Yoon, Eul-Sik
Summary Background A robotic surgery technique of harvesting the latissimus dorsi muscle flap has technical advantages over endoscopic harvest and cosmetic advantages over the open technique. The authors introduce a new transaxillary gasless technique using an articulated long retractor for robot assisted latissimus dorsi flap harvest. Methods Twelve robot assisted latissimus dorsi muscle flaps were harvested: 3 cases of delayed reconstruction following tissue expander insertion or breast conserving surgery; 4 cases of immediate reconstruction following nipple-sparing mastectomy; and 5 cases of chest wall deformity correction in patients with Poland syndrome. A specially designed articulated long retractor was used to maintain adequate working space and enable latissimus dorsi muscle dissection without gas insufflation. Results Twelve muscle flaps were successfully harvested in 12 patients without converting to an open technique. The mean docking time was 54.6 min, and the mean operative time and robotic time were 400.4 min and 85.8 min, respectively. There were no donor site complications or flap problems. Average follow-up was 15.7 months. All patients were satisfied with their esthetic results, especially the absence of visible scars. Conclusion The novel robot assisted latissimus dorsi harvest technique is a safe alternative to the conventional method.